Removing specification errors from the usual formulation of binary choice models - Paravastu A. V. B. Swamy; I-Lok Chang; Jatinder S. Mehta; William H. Greene; Stephen G. Hall; George S. Tavlas (Econometrics, 2016)
We develop a procedure for removing four major specification errors from the usual formulation of binary choice models. The model that results from this procedure is different from the conventional probit and logit models. This difference arises as a direct consequence of our relaxation of the usual assumption that omitted regressors constituting the error term of a latent linear regression model do not introduce omitted regressor biases into the coefficients of the included regressors.
Keywords: C13; C51; 330; binary choice models; specification errors; stochastic coefficients